THE EFFECT OF GROUP INVESTIGATION METHOD ON STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE - Yuni Khairina and Masitowarni Siregar (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2015)
This study is an attempt to discover the effect of applying Group Investigation Method on students’ achievement in writing descriptive text. It was conducted by using experimental research design. The Population of this research was the tenth (X) grade students of SMAN 11 Medan which consists of nine parallel classes with the total number of students is 286. The samples of this research were taken by random sampling through lottery technique. The result was class X IPA 1 consisted of 33 students became the experimental group and class X IPA 3 consisted of 31 students became the control group. The experimental group was taught by using Group Investigation Method while the control group was taught by using Conventional Method. The instrument for collecting the data was writing test. The data were analyzed by using t-test formula. The result shows that the value of t-observed (3.733) is higher than the value of t-table (2.000) (α = 0.05) with the degree of freedom (df) = 62. It means that there is a significant effect of applying Group investigation Method on students’ achievement in writing descriptive text. So, the alternative hypothesis (Ha) is accepted.